∼14 000 years of geochemical and isotopic data from Lake Simcoe, Canada - R.M. Doyle; N. Bumstead; C.F.M. Lewis; F.J. Longstaffe (Data in Brief, 2022)
This dataset contains measurements of modern water and ancient core materials from Lake Simcoe, the fourth largest lake wholly in Ontario, Canada. These data consist of: (i) oxygen, hydrogen and carbon isotope (δ18O, δ2H and δ13C) compositions for modern water samples; (ii) physical measurements of one piston core, PC-5; (iii) δ13C and δ18O values of ostracods collected from PC-5, and (iv) δ13C and δ18O values of ancient DIC and water, respectively, inferred from item (iii). Physical measurements performed on core PC-5 include magnetic susceptibility, mineralogy and grain size. Mass accumulation rates are also reported. These data will be of interest to those aiming to better characterize the timing and pathway of meltwater flow during and following deglaciation of the Laurentide Ice Sheet in the Laurentian Great Lakes region. These data will also be useful to researchers investigating the influence of deglaciation on the oxygen and carbon isotope systematics of ancient lake environments. A discussion of these data is available in “A ∼14 000-year record of environmental change from Lake Simcoe, Canada” [1].